Acute pancreatitis; etiopathogenetic and clinical research - İrfan SOYKAN,; Abdülkadir DÖKMECİ,; Hülya ÇETİNKAYA,; Ali Reşit Beyler,; Necati ÖRMECİ,; Mehmet BAŞTEMİR,; Ramazan IDILMAN,; Kadir BAHAR,; Selim KARAYALÇIN,; Cihan YURDAYDIN,; Özden UZUNALİMOĞLU, (Turkish Journal of Gastroenterology, 2020)
-